Adherence to a lifestyle programme in overweight/obese pregnant women and effect on gestational diabetes mellitus: a randomized controlled trial. Issue 3 (19th September 2016) - Bruno, Raffaele; Petrella, Elisabetta; Bertarini, Valentina; Pedrielli, Giulia; Neri, Isabella; Facchinetti, Fabio
Abstract: This study aims to determine whether the prescription of a detailed lifestyle programme in overweight/obese pregnant women influences the occurrence of gestational diabetes (GDM), and if this kind of prescription increases the adherence to a healthier lifestyle in comparison to standard care. The study was designed as a randomized controlled trial, with open allocation, enrolling women at 9–12 weeks of pregnancy with a BMI ≥ 25 kg/m 2 . The women assigned to the Intervention group (I = 96) received a hypocaloric, low‐glycaemic, low‐saturated fat diet and physical activity recommendations. Those assigned to the Standard Care group (SC = 95) received lifestyle advices regarding healthy nutrition and exercise. Follow‐up was planned at the 16 th, 20 th, 28 th and 36 th weeks. A total of 131 women completed the study (I = 69, SC = 62). The diet adherence was higher in the I (57.9%) than in the SC (38.7%) group. GDM occurred less frequently in the I (18.8%) than in the SC (37.1%, P  = 0.019) group. The adherent women from either groups showed a lower GDM rate (12.5% vs. 41.8%, P < 0.001). After correcting for confounders, the GDM rate was explained by allocation into the I group ( P  = 0.034) and a lower BMI category ( P  = 0.039). The rates of hypertension, preterm birth, induction of labour, large for gestational age babies and birthweight > 4000 g were significantly lower in I group. The incidence of small for gestational age babies was not different. These findings demonstrate that the adherence to a personalized, hypocaloric, low‐glycaemic, low‐saturated fat diet started early in pregnancy prevents GDM occurrence, in women with BMI ≥ 25 kg/m 2 .